Ponderal index of large-for-gestational age infants: comparison between infants of diabetic and non-diabetic mothers - Armangil, Didem; Yurdakök, Murat; Korkmaz, Ayşe; Yiğit, Sule; Tekinalp, Gülsevin (The Turkish Journal of Pediatrics, 2011)
Ponderal index (PI) is a weight-height related parameter that is mainly used to assess the pattern of fetal growth in small-for-gestational age infants. We aimed to use PI for large-for-gestational age (LGA) infants who were born to diabetic or non-diabetic mothers, in order to predict the fetal growth pattern. One hundred sixty-six LGA infants born at the Department of Obstetrics, Hacettepe University Hospital, Ankara, Turkey were included in the study. The PI was calculated by using the following formula: PI = weight (g) x 100/(height, cm)3. Sixty-seven (40%) of these infants were born to diabetic mothers. Maternal age, maternal weight and maternal weight gain during pregnancy were similar in the diabetic and non-diabetic groups. Mean birthweight, height and head circumference were similar in both groups, but median PI of infants of diabetic mothers was significantly higher than of infants of non-diabetic mothers (3.02 and 2.89, respectively, p < 0.05). Fetal growth was different between LGA infants of diabetic and non-diabetic mothers, and PI provided useful information on the proportionality of fetal growth in LGA infants.